The Influence of Financial Performance and Institutional Ownership on Disclosure of Corporate Social Responsibility: Empirical Study of The Companies Listed on Indonesia Stock Exchange in 2012 - Dwi Puryati (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
This research aims to determine whether the financial performance as measured by Debt to Equity Ratio, Current Ration and Return on Assets and institutional ownership have a significant effect on the disclosure of Corporate Social Responsibility. This research used corporate social disclosure index (CSDI) as an indicator of Corporate Social Responsibility disclosure by using the Global Reporting Initaatives (GRI). Research method used is descriptive and verification method. Population in this research was categorized as high-profile companies that were listed on the Indonesia Stock Exchange in 2012 totaling 189 companies. The sampling technique used was random sampling technique with iteration. The result was a company that became the research sample as many as 46 companies. The data used in this study was a secondary data obtained through the study of the documentation to get a company's annual report data form samples, idx statistics and Indonesian Capital Market Directory (ICMD) in 2012. Data analysis used multiple regressions. Classical assumption test used before regression of that includes normality test, heteroscedasticity, multicollinearity and autocorrelation. It also examined the hypothesis with the t-test and F-test to examine the influence of independent variables to the dependent variable. The result of data anlaysis indicated that Debt to Equity Ratio and Current Assets were partially no significant effect on the disclosure of Corporate Social Responsibility. Return on Assets and Institutional Ownership partially significant effect on the disclosure of Corporate Social Responsibility (CSR). And Debt to Equity Ratio, Current Assets, Return On Assset and Institutional Ownership simultaneously significant effected on the disclosure of Corporate Social Responsibility (CSR).Penelitian ini bertujuan untuk mengetahui apakah kinerja keuangan yang diukur dengan Debt to Equity Ratio, Current Ration and Return on Assets dan institutional ownership berpengaruh signifikan terhadap pengungkapan Corporate Social Responsibility. Penelitian ini menggunakan corporate social disclosure index (CSDI) sebagai indikator pengungkapan Corporate Social Responsibility dengan menggunakan Global Reporting Initiatives (GRI). Metode penelitian yang digunakan adalah metode deskriptif dan verifikatif. Populasi dalam penelitian ini dikategorikan sebagai perusahaan high-profile yang terdaftar di Bursa Efek Indonesia pada tahun 2012 sebanyak 189 perusahaan. Teknik sampling yang digunakan adalah teknik pengambilan sampel acak dengan iterasi. Hasilnya adalah perusahaan-perusahaan yang menjadi sampel penelitian adalah sebanyak 46 perusahaan. Data yang digunakan dalam penelitian ini adalah data sekunder yang diperoleh melalui dokumen laporan tahunan perusahaan public di IDX statistik dan Direktori Pasar Modal Indonesia (ICMD) tahun 2012. Analisis data yang digunakan regresi berganda. Uji asumsi klasik yang digunakan sebelum regresi yang meliputi uji normalitas, heteroskedastisitas, multikolinearitas dan autokorelasi. Selain itu juga meneliti hipotesis dengan t-test dan F-test untuk menguji pengaruh variabel independen terhadap variabel dependen. Hasil data anlaysis menunjukkan bahwa Debt to Equity Ratio dan Aktiva Lancar secara parsial tidak berpengaruh signifikan terhadap pengungkapan Corporate Social Responsibility. Return on Assets dan Kepemilikan Institusional secara parsial berpengaruh signifikan terhadap pengungkapan Corporate Social Responsibility (CSR). Selain itu Debt to Equity Ratio, Aktiva Lancar, Return on Assset dan Kepemilikan Institusional secara bersamaan signifikan berpengaruh terhadap pengungkapan Corporate Social Responsibility (CSR).